Study of Current Instability Testing in Andongan In 150 Kva High Voltage Air Line - Riza Effendi Wijaya; Adi Sastra P Tarigan; Solly Aryza (Eduvest - Journal of Universal Studies, 2022)
Air transmission lines generally use ACSR type conductors. As the demand for electrical energy increases, the effort to increase the capacity of the transmission line is carried out by optimizing the current-carrying capacity of the existing transmission line, but the problem that arises in this optimization is the increase in the voltage and slope of the conductor. This study aims to determine the effect of line current instability on conductor temperature, conductor slope, slope angle and conductor voltage, which is then useful for the construction of transmission line construction structures in accordance with the mechanical properties of the conductors used. This study uses the calculation of the heat balance equation. to calculate the conductor temperature. The Basic Span Length method is used to determine the equivalent span length